2019
DOI: 10.46886/ijarp/v6-i1/6393
|View full text |Cite
|
Sign up to set email alerts
|

Parental Experiences with Duchenne Muscular Dystrophy: Feelings of loss and Empowerment

Abstract: Muscular dystrophies are a heterogeneous group of mainly hereditary diseases that affect the functioning of the muscle system. Few studies have focused on the psychological adjustment of parents of children with Duchenne muscular dystrophy. This study's objective was to investigate the parents' experience and the process of adjustment to the complex nature of their child's disorder. The study used a qualitative research design. Qualitative thematic analysis was used to analyze the data collected from parents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They emphasized the importance of sharing frustrations and burdens with those who could empathize, whether within a support group or among friends and family. Research by Koufaki and colleagues (2019) indicated that parents who take sole responsibility for their children’s care may limit their social interactions, leading to heightened social isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasized the importance of sharing frustrations and burdens with those who could empathize, whether within a support group or among friends and family. Research by Koufaki and colleagues (2019) indicated that parents who take sole responsibility for their children’s care may limit their social interactions, leading to heightened social isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this is underscored by the emergent theme that AYAs were frequently unprepared to make health‐related decisions due to lack of experience. At the same time, the present‐day focus may, as Koufaki and colleagues note, be a way parents seek to control emotions related to an uncertain future for their child 23 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the present-day focus may, as Koufaki and colleagues note, be a way parents seek to control emotions related to an uncertain future for their child. 23 Several caregivers described mistrust in the health care system, based on their experience with what they perceived to be a lengthy diagnostic process, finalized as late as five years old. This sense of mistrust persisted over time, with caregivers citing a preference to pay a private lawyer to draw up ADs rather than complete the freelyavailable versions available at the hospital.…”
Section: Discussionmentioning
confidence: 99%